These men in love with mining companies and pickup trucks: Moralities and knowledge practices of the deserts and movements of the economy - André Dumans Guedes (Vibrant: Virtual Brazilian Anthropology)
Abstract: This article’s protagonists are traders and small businesspeople who express their enthusiasm for the start-up of a mining company while admiring the pickup trucks that such an enterprise circulates in a city in the north of the Brazilian state of Goiás. I place the perspectives of these men in a story organized by the fear that this locality becomes a ‘desert’, then consider how they have been relating to recent transformations in the ‘economy’ of this city. I thus bring to the foreground certain moral dimensions of their lives and occupations and the role of pickup trucks as signs and operators of the knowledge practices to which they resort to situate themselves in the face of both long-standing anxieties and these new realities. Finally, I show how this ‘economy of the city’ is outlined by an interweaving of certain branches and productive activities with practices, stories, circulations, rivalries that are markedly masculine, and which are updated in those places and paths where pickup trucks are present.